Genotypic and phylogeographic insights into a pre-epidemic variant of Wesselsbron virus detected in sylvatic Aedes mcintoshi from Semuliki Forest, Uganda - Georg Joachim Eibner; Selina Laura Graff; Christian Hieke; James Robert Ochieng; Anne Kopp; Christian Drosten; Julius Lutwama; Innocent Bidason Rwego; Sandra Junglen (Microbiology Spectrum)
ABSTRACT Wesselsbron virus (WSLV) is a neglected mosquito-borne virus within the yellow fever subgroup in the genus Orthoflavivirus of the Flaviviridae family. Despite being primarily a veterinary pathogen able to cause stillbirths, congenital malformations, and mortality in ruminants, WSLV also infects humans, causing a usually self-limiting febrile illness, or may lead to neurological complications in rare cases. WSLV causes sporadic outbreaks in Southern Africa, but findings in mosquitoes from other African countries suggest a wider distribution. Here, we report the detection and isolation of WSLV from an Aedes mcintoshi mosquito collected in a pristine ecosystem within Semuliki National Park, western Uganda. The detected strain M5937-UG-2018 was impaired in infectivity, replication, and production of infectious particles in cell lines derived from different hosts compared to an epidemic reference strain, SA H177. Full-genome sequencing by next-generation sequencing from the mosquito homogenate revealed a maximum nucleotide identity of 98.1% to a WSLV isolate from a human sample collected in South Africa in 1996. M5937-UG-2018 grouped in phylogenetic analyses with strains from South Africa and Senegal. Reconstruction of the temporal and spatial dispersal of WSLV across Africa estimated a likely origin of WSLV in South Africa in the early 19th century and spread in Southern Africa in the following decades. Long-distance movement toward Western and Eastern Africa was modeled to have occurred in the early 21st century. However, displacing the origin of M5937-UG-2018 did not decrease the likelihood of the model supporting the hypothesis that WSLV is widely distributed in Africa.IMPORTANCEWSLV is a neglected mosquito-borne virus causing teratogenicity in ruminants and febrile illness in humans. WSLV is mainly endemic to Southern Africa, but findings in other regions suggest a wider distribution on the continent. Knowledge of the distribution of WSLV is impaired as differential diagnostics are rarely performed in livestock and humans presenting with symptoms compatible with WSLV infection. Our work investigating viral infections in mosquitoes from a remote tropical rainforest region demonstrates that WSLV is endemic in Uganda. The isolated virus was less infective and showed lower replication ability in vitro compared to an epidemic isolate from South Africa. Phylogeographic reconstruction of spatial and temporal movements, along with the displacement of the origin of the newly detected strain, suggests that WSLV may be widely distributed across Africa. Our data show that the geographic distribution of WSLV and its impact on human and animal health are likely underestimated.